2021
DOI: 10.1177/14574969211030131
|View full text |Cite
|
Sign up to set email alerts
|

The liver-first approach for synchronous colorectal liver metastases: A systematic review and meta-analysis of completion rates and effects on survival

Abstract: Background: Patients presenting with synchronous colorectal liver metastases are increasingly being considered for a curative treatment, and the liver-first approach is gaining popularity in this context. However, little is known about the completion rates of the liver-first approach and its effects on survival. Methods: A systematic review and meta-analysis of liver-first strategy for colorectal liver metastasis. The primary outcome was an assessment of the completion rates of the liver-first approach. Second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…All areas of the hemiliver, sectors, and Couinaud's segments were represented as an aggregation of voxels classified with each of the three attributes (hemiliver [left or right], sector [posterior, anterior, medial and lateral], and segment [1][2][3][4][5][6][7][8] ) on the 3D simulation data as shown in Fig- ure 2c. Attribution of these voxels for the Pure-and Semi-AI groups, and GT data were compared to determine the true positive, false positive, and false negative rates, and the similarities among the Pure-and Semi-AI groups, and the GT data.…”
Section: Accuracy Of Automated Segmentationmentioning
confidence: 99%
See 2 more Smart Citations
“…All areas of the hemiliver, sectors, and Couinaud's segments were represented as an aggregation of voxels classified with each of the three attributes (hemiliver [left or right], sector [posterior, anterior, medial and lateral], and segment [1][2][3][4][5][6][7][8] ) on the 3D simulation data as shown in Fig- ure 2c. Attribution of these voxels for the Pure-and Semi-AI groups, and GT data were compared to determine the true positive, false positive, and false negative rates, and the similarities among the Pure-and Semi-AI groups, and the GT data.…”
Section: Accuracy Of Automated Segmentationmentioning
confidence: 99%
“…Liver cancer is the third leading cause of cancer death, with an estimated 0.8 million deaths in 2020 1 . Hepatectomy is crucial treatment for liver cancer 2 and colorectal liver metastases 3 . To ensure a safe hepatectomy and avoid postoperative liver failure, preoperative virtual hepatectomy with three‐dimensional (3D) simulation has become the standard procedure for surgical planning and intraoperative navigation to precisely estimate the liver resection volume 4,5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For staged strategies, a “conventional approach” will suggest removal of the primary tumor first (either colon or rectal cancer) and plan for liver surgery after recovery of the first operation. A “Liver first” or reversed strategy will prioritize the liver resection first [ 9 , 10 ]. Arguments have been put forward that a “liver-first” strategy is associated with improved survival [ 11 ], but such improved survival figures usually relate to those who actually are resected and “intention to treat” is often neglected in these comparative studies.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that about 50% of colorectal cancer patients may have liver metastases during the course of the disease. Of these, 15-25% have synchronous liver metastases [5]. Even after achieving curative resection of the primary tumor of colorectal cancer, the chance of developing metachronous liver metastases is as high as 30% [3].…”
Section: Introductionmentioning
confidence: 99%